The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0260464
|View full text |Cite
|
Sign up to set email alerts
|

Physical-mental health comorbidity: A population-based cross-sectional study

Abstract: Background Multimorbidity is associated with physical-mental health comorbidity (PMHC). However, the scope of overlap between physical and mental conditions, associated factors, as well as types of mental illness involved are not well described in Eastern Europe. This study aims to assess the PMHC burden in the Estonian population. Methods In this population-based cross-sectional study we obtained health claims data for 55 chronic conditions from the Estonian Health Insurance Fund (EHIF) database, which capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…Specifically, participants with a higher number of physical conditions exhibited greater odds of experiencing anxiety and/or mood disorders. Our results agreed with the existing literature that offers insights into various mechanisms through which physical and mental health mutually influence each other, including pain, worry, functional limitations, and lifestyle modifications (Baghdadi et al, 2021; Gabilondo et al, 2012; Jurisson et al, 2021; Scott et al, 2016; Tsang et al, 2008). These findings hold particular significance within the Saudi context for two main reasons.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, participants with a higher number of physical conditions exhibited greater odds of experiencing anxiety and/or mood disorders. Our results agreed with the existing literature that offers insights into various mechanisms through which physical and mental health mutually influence each other, including pain, worry, functional limitations, and lifestyle modifications (Baghdadi et al, 2021; Gabilondo et al, 2012; Jurisson et al, 2021; Scott et al, 2016; Tsang et al, 2008). These findings hold particular significance within the Saudi context for two main reasons.…”
Section: Discussionsupporting
confidence: 90%
“…The highest prevalence of somatic comorbidities among participants in this study was CVD, predominantly hypertension and coronary heart disease. Notably, the prevalence of comorbidities in this study was substantially higher than in a population‐based cross‐sectional study (13.1%) 27 . Another large sample study reported that the prevalence of multimorbidities substantially increased with age and was present in most people aged 65 years and older 28 .…”
Section: Discussioncontrasting
confidence: 75%
“…Notably, the prevalence of comorbidities in this study was substantially higher than in a populationbased cross-sectional study (13.1%). 27 Another large sample study reported that the prevalence of multimorbidities substantially increased with age and was present in most people aged 65 years and older. 28 Hypertension, chronic lung disease, and the number of comorbidities were associated with hospital readmissions in PMI, according to the results of a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…Junior doctors have shared dissatisfaction with handover arrangements within mental health hospitals 9. Meanwhile, the complexity of psychiatric disorders has been escalating,10–12 and load of physical and mental health comorbidities has been growing 13 14. There arises a necessity to apply equally robust clinical handover practices within inpatient psychiatric settings.…”
Section: Introductionmentioning
confidence: 99%